Mapping of Sea Surface Temperatures on The Coast Probolinggo With Satellite Image Data - Husen Bin Novel Syamlan; Siti Zainab (CV. Syntax Corporation Indonesia, 2023)
Indonesia has the advantage of abundant marine resources. One of them is on the coast of Probolinggo , where the average community there utilizes marine natural resources for livelihoods. Monitoring ocean conditions such as sea surface temperature (SST) is used to facilitate and streamline the utilization of marine resources, namely by using remote sensing technology from Aqua MODIS satellite images which can later be used as a database in the field of Civil Engineering in the planning and construction of water buildings such as ports and docks. In this study, it can be used for SPL mapping using field data ( in situ ) and data from Aqua MODIS satellite imagery with the help of the SeaDAS application. The data used from Aqua MODIS satellite imagery is data from 2019-2023, with wavelengths of 412 nm, 531 nm and 667 nm. The results of the analysis and discussion of satellite image data concluded that the best data is the 2023 image data. For SPL with a wavelength of 531 nm, the logarithmic equation with the SPL = 3.7797ln(x) + 51.436 algorithm model, R 2 value = 0.1201 and correlation value R = 0.4567300 which has a moderate positive correlation.